The Effect of Addition Red Passion Juice (Passiflora Edulis) on Fat Content, Protein Content, and Eastness of Mozzarella Cheese - Surtina, Dara; Asri, Alfian; Hanifatunnisa, Hanifatunnisa (Journal of Animal Nutrition and Production Science, 2023)
This research aimed to determine the effect of adding red passion fruit juice (Passiflora edulis) on fat content, protein content, and elongation of mozzarella cheese. This research used an experimental method with a Completely Randomized Design with 4 treatments, namely giving red passion fruit (Passiflora edulis) (0%, 6%, 8%, and 10%) with 4 repetitions. The research results on the average fat content for each treatment were, P0 (15.97%), P1 (15.33%), P2 (13.25%), and P3 (12.69%). protein is P0 (21.70%), P1 (22.29%), P2 (23.24%), P3 (23.86%). The results of the research on the average elongation are, P0 (66.50cm), P1 ( 83.50cm), P2 (85.25cm), and P3 (91.25cm). Based on the research results it can be concluded that giving red passion fruit juice (Passiflora edulis) has a very significant effect (P<0.01) on fat content and protein content and was not significantly different (P>0.05) on the elongation of mozzarella cheese. The best treatment was found in the treatment without the addition of red passion fruit juice (Passiflora edulis) for protein and fat content while the best elongation was obtained in the treatment with the addition of 10% red passion fruit juice (Passiflora edulis).